Clinical learning environment of nursing and midwifery students in Ghana - Florence Assibi Ziba; Vida Nyagre Yakong; Zakari Ali (BMC, 2021)
Abstract Background Data on student experience of the clinical learning environment in Ghana are scarce. We therefore aimed to assess students' evaluation of the clinical learning environment and the factors that influence their learning experience. Methods This was a cross-sectional survey of 225 undergraduate nursing and midwifery students. We used the Clinical Learning Environment and Supervision + Nurse Teacher (CLES +T) evaluation scale to assess students' experience of their clinical placement. The association between student demographic characteristics and clinical placement experience was determined using t-test or ANOVA. Results Most of the sampled students were Nurses (67%) and in the third year of training (81%). More students received supervision from a nurse (57%) during clinical placement and team supervision (67%) was the most common during clinical placement. Nursing students were more likely to rate their clinical experience better than midwifery students (p=0.002). Students who had increased contact with private supervisors were also more likely to rate their experience higher (p=0.002). Clinical experience was also rated higher by students who received successful supervision compared to those who had unsuccessful or team supervision (p=0.001). Conclusion Team supervision is high in health facilities where students undertake clinical placement in Ghana. Frequent contact with private supervisor and successful supervision are associated with better rating of clinical experience among Ghanaian undergraduate nursing and midwifery students.